Germ Line/Multipotency Genes Show Differential Expression during Embryonic Development of the Annelid Enchytraeus coronatus - Roman P. Kostyuchenko; Daria D. Nikanorova; Artem V. Amosov (Biology, 2023)
Germ line development and the origin of the primordial germ cells (PGCs) are very variable and may occur across a range of developmental stages and in several developmental contexts. In establishing and maintaining germ line, a conserved set of genes is involved. On the other hand, these genes are expressed in multipotent/pluripotent cells that may give rise to both somatic and germline cells. To begin elucidating mechanisms by which the germ line is specified in Enchytraeus coronatus embryos, we identified twenty germline/multipotency genes, homologs of Vasa, PL10, Piwi, Nanos, Myc, Pumilio, Tudor, Boule, and Bruno, using transcriptome analysis and gene cloning, and characterized their expression by whole-mount in situ hybridization. To answer the question of the possible origin of PGCs in this annelid, we carried out an additional description of the early embryogenesis. Our results suggest that PGCs derive from small cells originating at the first two divisions of the mesoteloblasts. PGCs form two cell clusters, undergo limited proliferation, and migrate to the developing gonadal segments. In embryos and juvenile E. coronatus, homologs of the germline/multipotency genes are differentially expressed in both germline and somatic tissue including the presumptive germ cell precursors, posterior growth zone, developing foregut, and nervous system.